Cortical superficial siderosis, hematoma volume, and outcomes after intracerebral hemorrhage: a mediation analysis - Jin, Yu-jia; Li, Jia-wen; Wu, Jian; Huang, Yu-hui; Yang, Kai-cheng; An, Hong-na; Yuan, Chang-zheng; Gao, Feng; Tong, Lu-sha (Frontiers in Neurology, 2023)
Background Previous studies have shown that cortical superficial siderosis (cSS) can increase hematoma volume and predict poor outcomes following primary intracerebral hemorrhage (ICH). Objective We aimed to determine whether a large hematoma volume was the essential factor contributing to worse outcomes of cSS. Methods Patients with spontaneous ICH underwent a CT scan within 48 h after ictus. Evaluation of cSS was performed using magnetic resonance imaging (MRI) within 7 days. The 90-day outcome was assessed using the modified Rankin Scale (mRS). In addition, we investigated the correlation between cSS, hematoma volume, and 90-day outcomes using multivariate regression and mediation analyses. Results Among the 673 patients with ICH [mean (SD) age, 61 (13) years; 237 female subjects (35.2%); median (IQR) hematoma volume, 9.0 (3.0–17.6) ml], 131 (19.5%) had cSS. There was an association between cSS and larger hematoma volume (β = 4.449, 95% CI 1.890–7.009, p < 0.001) independent of hematoma location and was also related to worse 90-day mRS (β = 0.333, 95% CI 0.008–0.659, p = 0.045) in multivariable regression. In addition, mediation analyses revealed that hematoma volume was an essential factor mediating the effect of cSS on unfavorable 90-day outcomes (proportion mediated:66.04%, p = 0.01). Conclusion Large hematoma volume was the major charge of directing cSS to worse outcomes in patients with mild to moderate ICH, and cSS was related to a larger hematoma in both lobar and non-lobar areas. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT04803292, identifier: NCT04803292.